IMPLEMENTASI PROGRAM BIMBINGAN KARIR DALAM KURIKULUM MERDEKA BELAJAR DI SMKN 3 MADIUN - Wicaksono, Aditya Yudha; Trisnani, Rischa Pramudia; Sari, Qonik Kus Armanda (Universitas Muria Kudus, 2024)
This study aims to find out the first, to find out the level of student career planning when the career guidance program is in the independent learning curriculum, the second is whether there is a difference after being given a career guidance program in the independent learning curriculum. This research is a descriptive qualitative research. The subjects of this study included school principals, deputy principals for curriculum, vice principals for student affairs, counseling teachers and students at SMKN 3 Madiun. Data collection methods used are observation, interviews, and documentation. From the results of this study it can be seen First; The implementation of the counseling program at SMKN 3 Madiun is quite good. Judging from the implementation of information services where the teacher always provides information about the world of work and the industrial world, the counseling teacher always provides counseling services to their students through class hours determined by the classical service method, the counseling teacher is also ready to provide individual counseling services when there are students who experience problems. . Second; The implementation of the Merdeka Curriculum at SMKN 3 Madiun was carried out well. Judging from the curriculum program that has been implemented and compiled by several teachers, it is sufficient to facilitate the implementation of learning for teachers and streamline learning or material provided to students. Supporting factors for the implementation of student career planning are categorized as quite good, schools always support the implementation of student career planning by carrying out several activities such as EduFair or JobFair to determine student career plans whether they want to continue on to higher education or the world of work.